Solvent-tuned dual emission: a structural and electronic interplay highlighting a novel planar ICT (OPICT)1. Issue 12 (28th March 2015) - Chevreux, S.; Paulino Neto, R.; Allain, C.; Nakatani, K.; Jacques, P.; Ciofini, I.; Lemercier, G.
<x xml:space="preserve">Abstract</x> Displaying a dual emission, a Phen-PENMe2 compound can be foreseen as a new model for fundamental studies.